Analisis Perbandingan Konsep Perkembangan Kognitif Perspektif Al-Ghazali Dan Jean Piaget - Muhammad Romdon (Oasis : Jurnal Ilmiah Kajian Islam, 2023)
Al-Ghazali and Jean Pigaet have a lot in common regarding cognitive or intellectual discussions, both of which divide into four stages. In this study the aim is to examine the views of these two figures who have correlation points of contact on the experience aspects of each stage in the process of cognitive or intellectual development. The research method used is the philosophical comparative comparison method, systematic discussion takes place according to schemes or stages: 1) describing each concept, 2) looking for similarities and differences in each of the two figures, and 3) criticizing the two thoughts. The difference in Al-Ghazali's thought is that he took the path of experience in ratios originating from revelation, while Jean Piaget took an experience as the basis for his thoughts on the purity of ratios. In addition, there are also differences in their views on the use of the term, reason is the name of cognition given by Al- Ghazali while Jean Piaget calls it a cognitive expression.